Using Manual and Automatic Summarization: What Should Students Consider in Writing a Summary? - Tira Nur Fitria (English Language and Education Spectrum, 2023)
Writing a summary related to reading and writing. Writing a summary of a text not only helps students assimilate what they have read by highlighting and connecting the key points but also enables them to articulate their thoughts in writing. It means that a summary must be brief, accurate, and written in individual words. This study describes teaching summarization both manual and automatic summarization for students. This research is library research. The analysis shows that writing and summarizing a journal article is a common task for students. Students can read articles for summaries, plan good summaries, and write summaries to completion. Writing a summary can be manual or online (automatic) summarization. Manually, students need to consider several points before writing a summary including avoiding using personal pronouns, making sentences as objective as possible, beginning by defining the problem statement, discussing the author’s methodology, describing the research results, connecting the main ideas featured, do not conclude, provide the interpretation, avoid using direct quotes from journal articles, use appropriate tenses and improve students writing design. Students must check their self-evaluation of summarising skills, such as expressing the central idea or theme as a statement/declarative, assessing the quantity, quality, and order of the evidence, constructing evidence for inferential reasoning, paraphrasing details in their words, and avoiding common pitfalls. While automatic summarisation involved an online summarizer tool. Many summarization tools are available for English languages with abundant resources. However, students need to consider the benefits and the limitations.